1978
DOI: 10.1111/j.1745-4549.1978.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Oxygen Through Ice and Frozen Minced Fish

Abstract: The storage life of frozen fish depends, in part, on quality degradation due to oxidation of lipids. In minced fish products, transport of oxygen through the frozen material is one possible mechanism for supplying the required oxygen to the reactive lipids. Oxygen transport through ice and minced fish at —5°C was determined using a Clark‐type oxygen electrode in a sample of known geometry. Oxygen permeability of ice appeared related to physical defects of the ice samples. Fast frozen ice had widely varying per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This finding is in agreement with the autocatalytic nature of the lipid oxidation process (Belitz and Grosch, 1987). Second, the data point to limited oxygen availability in the interior of the fillets during storage (Flink and Goodhart, 1978;Undeland et al, 1998a,c,d). Although the initial pro-oxidative activity ranked the three layers as follows, under skin > middle part > inner part, a limited diffusion of oxygen trough the tissue appeared to supress the significance of pro-oxidants for hydroperoxide formation in the middle layer.…”
Section: Resultsmentioning
confidence: 98%
“…This finding is in agreement with the autocatalytic nature of the lipid oxidation process (Belitz and Grosch, 1987). Second, the data point to limited oxygen availability in the interior of the fillets during storage (Flink and Goodhart, 1978;Undeland et al, 1998a,c,d). Although the initial pro-oxidative activity ranked the three layers as follows, under skin > middle part > inner part, a limited diffusion of oxygen trough the tissue appeared to supress the significance of pro-oxidants for hydroperoxide formation in the middle layer.…”
Section: Resultsmentioning
confidence: 98%
“…Since the packaging box provided almost no barrier to oxygen, it was concluded that diffusion of oxygen was limited by the mince itself. According to Flink and Goodhart (1978), oxygen diffusion trough frozen fish mince is retarded due to plugging of the oxygen transport pathways and therefore is highly dependent upon sample thickness. Virtually no oxygen diffusion could be measured in frozen fish mince samples thicker than 5 mm, supporting the present observations.…”
Section: Resultsmentioning
confidence: 99%